Understanding the role of toggle genes in chronic lymphocytic leukemia proliferation - Olga Sirbu; Gunjan Agarwal; Alessandro Giuliani; Kumar Selvarajoo (npj Systems Biology and Applications)
Abstract Cancer cell populations, such as chronic lymphocytic leukemia (CLL), are characterized by aberrant proliferation and plasticity: cells may switch between states so increasing population heterogeneity. Previous works have shown that gene expression noise can impact cell-state transition. To gain better insights into transcriptome-wide expression dynamics and the effect of noise on state transition, here we investigate RNA-Seq data of proliferative (PC) and non-proliferative (NPC) CLL cells. Various data analytics were applied to the whole transcriptome, switch-like toggle (ON/OFF) genes, temporal differentially expressed (DE) genes, and randomly selected genes. Collectively, we identified 2713 temporal DE genes (DESeq2 with 4-fold, p < 0.05) and 1704 toggle genes shaping the differentiation process over a period of 96 h, with 604 overlapping genes between them. Despite their lower numbers compared to DE, toggle genes contributed significantly to gene expression noise in both cell types. Toggle gene analyses revealed the enrichment of genes involved in processes such as G-alpha signaling and muscle contraction as proliferation related RHO-GTPase, interleukin and chemokine signaling, and lymphoid cell communication. Thus, toggle genes, although being random ON/OFF genes, show gene expression functional variability. These results suggest that toggle genes play an important role in shaping cell population plasticity.